Acceptability of Bedside Resuscitation With Intact Umbilical Cord to Clinicians and Patients’ Families in the United States - Katheria, Anup C.; Sorkhi, Samuel R.; Hassen, Kasim; Faksh, Arij; Ghorishi, Zahra; Poeltler, Debra (Frontiers in Pediatrics, 2018)
Background: While delayed umbilical cord clamping in preterm infants has shown to improve long term neurological outcomes, infants who are thought to need resuscitation do not receive delayed cord clamping even though they may stand to benefit from it more. A mobile resuscitation platform allows infants to be resuscitated at the mother’s bedside with the cord intact. The newborn is supplied with placental blood during the resuscitation in view of the mother. The objective of the study is to assess the usability and acceptability of mobile resuscitation platform, LifeStart trolley, among the infants’ parents and perinatal providers. Methods: A resuscitation platform was present during every delivery that required advanced neonatal providers for high risk deliveries. Perinatal providers and parents of the infants were given a questionnaire shortly after the delivery. Results: 60 neonatal subjects were placed on the trolley. The majority of deliveries were high risk for meconium-stained amniotic fluid (43%), and non-reassuring fetal heart rate (45%). About 50% of neonatal providers felt that there were some concerns regarding access to the baby. No parents were uncomfortable with the bedside neonatal interventions, and most parents perceived that communication was improved because of the proximity to the care team. Conclusion: Bedside resuscitation with umbilical cord intact through the use of a mobile resuscitation trolley is feasible, safe, and effective, but about half of perinatal providers expressed concerns. Logistical issues such as improved space management and/or delivery setup should be considered and centers planning to perform neonatal resuscitation with an intact cord.